1986
DOI: 10.1038/jcbfm.1986.99
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of a Quantitative Cerebral Blood Flow Measurement Using H215O Autoradiography and Positron Emission Tomography, with Respect to the Dispersion of the Input Function

Abstract: The effect of the inaccuracy of the input function on CBF measured by the H2(15)O autoradiographic method was investigated. In H2(15)O autoradiography the measured input function usually includes a larger dispersion than the true input function, as well as the absolute time axis having been already lost. The time constant of the external dispersion that occurred in our continuous sampling system was evaluated as 10-12 s when the dispersion function was approximated by a monoexponential function. The internal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
184
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(189 citation statements)
references
References 15 publications
5
184
0
Order By: Relevance
“…The value of dispersion coefficient within the radial artery and/or cannula estimated by each study duration to those for the total study period of 10 min are shown. Iida et al (1986) is of the same order of magnitude as the values obtained in the present study. A major advantage of the build-up technique is therefore the capability to measure this dispersion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The value of dispersion coefficient within the radial artery and/or cannula estimated by each study duration to those for the total study period of 10 min are shown. Iida et al (1986) is of the same order of magnitude as the values obtained in the present study. A major advantage of the build-up technique is therefore the capability to measure this dispersion.…”
Section: Discussionsupporting
confidence: 87%
“…Dispersion within the radial artery and/or cannula might also explain the discrepancy between rCBF values obtained from autoradiographic and steady state techniques (Kanno et al, 1984) as indicated by Iida et al (1986). The value of dispersion coefficient within the radial artery and/or cannula estimated by each study duration to those for the total study period of 10 min are shown.…”
Section: Discussionmentioning
confidence: 98%
“…Values for CBF, OEF, and CMRO 2 were calculated based on three-step ARG and DARG. To shift the dispersion time constants, the true arterial TAC was convoluted or deconvoluted with a simple exponential (Iida et al, 1986;Kanno et al, 1987). For simulating the error in the values of p and V B , the value of p was varied from 0.7 to 0.9 mL/g, and that of V B from 0.02 to 0.06 mL/g; in each situation, tissue TACs were created and CBF, OEF, and CMRO 2 values were calculated using these TACs, assuming P ¼ 0.8 mL/g and V B ¼ 0.04 mL/g.…”
Section: Error Analyses In Simulationmentioning
confidence: 99%
“…The regional CBF and OEF were measured during continuous and consecutive 9-min inhalations of C 15 O 2 and 15 O 2 with continuous arterial blood sampling, employing a table-lookup technique (Senda et al, 1988). The regional CBF and OEF were obtained by calculating the values with lookup tables created from the arterial whole blood and plasma radioactivity curves, and then correcting them for delay and dispersion (Iida et al, 1986). The CBV was measured by a 3-min inhalation of C 15 O with blood sampling (Grubb et al, 1978).…”
Section: O Gasesmentioning
confidence: 99%